Acute appendicitis in pediatric patients with Coronavirus Disease 2019 (COVID-19): A case series from a developing country’s tertiary hospital - Nurnaningsih, Nurnaningsih; Danudibroto, Gladys Indika; Rusmawatiningtyas, Desy; Kumara, Intan Fatah; Makrufardi, Firdian; Widowati, Titis (Elsevier BV, 2022)
Introduction: and importance: A common gastrointestinal presentation of both COVID-19 and multisystem in- flammatory syndrome in children (MIS-C) is acute abdominal pain, which sometimes mimics appendicitis. Literature describing children with COVID-19 infection and concurrent acute appendicitis is growing, and understanding these patients’ clinical picture is necessary for their proper treatment. Case presentation: We present a case series of six healthy children before they developed classic symptoms of appendicitis. At the same time, they were also found to have confirmed COVID-19. All patients had fever and right lower abdominal pain. Four of six children having Alvarado score above seven had surgical treatment, while the others only received systemic antibiotic and antiviral medication. Surgical results of two patients revealed perforated appendicitis. No mortality occurred among them. Clinical discussion: There is increasing recognition of gastrointestinal involvement in patients with COVID-19 and MIS-C. There are several postulates to explain appendicitis in COVID-19. First, inflammatory response is exaggerated in SARS-CoV-2 infected patients. Second, obstruction of the appendiceal lumen is caused by mesenteric adenopathy, which in turn, is caused by COVID-19 infection, not fecalith. Third, hyperinflammatory response in MIS-C triggers inflammation in appendix. Conclusion: Clinicians must recognize that abdominal pain with fever could be the presenting symptoms of COVID-19 with MIS-C. MIS-C, which has severe presentations with gastrointestinal manifestations and high mortality rate, should be considered as a differential diagnosis for a patient with appendicitis-like symptoms and a positive SARS-CoV-2 infection.